Evaluation of Hydrodynamic Conditions in the Oualidia Lagoon (Atlantic Coast of Morocco) - Mohammed Bouchkara; Khalid El Khalidi; Nouhaila Erraji Chahid; Imane Joudar; Vladimir Koutitonsky; Aïssa Benazzouz; Abdenaim Minoubi; Bendahhou Zourarah (Proceedings)
The present study is based on the combination of field measurements with Copernicus Marine Service (CMS) data and numerical modeling approaches to assess the historical and actual variations of ocean parameters in the Oualidia lagoon in Morocco, including tides, waves, currents and winds. The lagoon of Oualidia is a site of ornithological importance; it has been classified as a site of biological and ecological interest (S.I.B.E), through the Master Plan of Protected Areas, and as a RAMSAR site since 2005. This lagoon has undergone significant anthropogenic modifications in recent years, which included the creation of a sediment trap in 2011 and a dike opening upstream in 2005. The objective of this research is to evaluate the hydrodynamic conditions of this lagoon and its open sea area (offshore) using field measurements, numerical modeling and ocean data collected from Marine Copernicus Service platform. As a result, the analysis of wind data for the year 2021 shows that the prevailing winds are generally northwest, from north to northeast, with a very strong predominance of north to northeast winds. The harmonic analysis of tides for the same period showed that the lagoon is dominated by an M2 tide component with an amplitude reaching 0.9649 m. In addition, the results of the analysis of waves in front of the lagoon of Oualidia revealed a predominance of waves of height ranging between 1 and 2.5 m, representing nearly 60% of the model outputs. Waves with a height of from 3 to 4 m represent 10% of the results, while large winter waves (>4 m) represent only 3%. In addition, the analysis of current data (in situ/modeled) indicates that the current velocities decrease from the downstream to upstream area, in relation to the variations in and the period of tides that affect the variability of tidal currents inside of the lagoon.